Hypermutability bypasses genetic constraints in SCV phenotypic switching in Pseudomonas aeruginosa biofilms - Romina A. Tobares; Román A. Martino; Claudia A. Colque; Gaston L. Castillo Moro; Alejandro J. Moyano; Andrea G. Albarracín Orio; Andrea M. Smania (npj Biofilms and Microbiomes)
Abstract Biofilms are critical in the persistence of Pseudomonas aeruginosa infections, particularly in cystic fibrosis patients. This study explores the adaptive mechanisms behind the phenotypic switching between Small Colony Variants (SCVs) and revertant states in P. aeruginosa biofilms, emphasizing hypermutability due to Mismatch Repair System (MRS) deficiencies. Through experimental evolution and whole-genome sequencing, we show that both wild-type and mutator strains undergo parallel evolution by accumulating compensatory mutations in factors regulating intracellular c-di-GMP levels, particularly in the Wsp and Yfi systems. While wild-type strains face genetic constraints, mutator strains bypass these by accessing alternative genetic pathways regulating c-di-GMP and biofilm formation. This increased genetic accessibility, driven by higher mutation rates and specific mutational biases, supports sustained cycles of SCV conversion and reversion. Our findings underscore the crucial role of hypermutability in P. aeruginosa adaptation, with significant implications for managing persistent infections in clinical settings.